El Excentrico, 1979-06-20 & 1979-07-05 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
June 20 & July 5, 1979 [20 de junio y 5 de julio de 1979]. Ano 30, No 6. Cover contains Bert Garcia with Lucha Villa, who would be performing at a county fair for the Fourth of July 1979.